Rhythmic intricacies: a study of Lansky, Delécluse, Xenakis, Koppel, and Hamilton - Adams, Brandon E. (Kansas State University, 2022)
The study includes a rhythmic style analysis of compositions that I performed on my master’s recital on May 11th, 2019. Jan LaRue’s Guidelines for Style Analysis is the basis for this study. LaRue’s basic components for analytic hypothesis are sound, harmony, melody, rhythm, and growth. The compositions that were studied were Three Moves for Marimba by Paul Lansky, Etude 9 from Douze Études pour Caisse-Claire by Jacques Delécluse, Rebonds “b” by Iannis Xenakis, Toccata for Vibraphone and Marimba by Anders Koppel, and Rituals by Bruce Hamilton.
Keywords: Music theory; Rhythmic analysis